Interaksi Sosial Lansia dalam Aktivitas Harian di Sentra “Gau Mabaji” Kabupaten Gowa - Nurannisa Lumanto; Najamuddin Najamuddin; Supriadi Torro (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze: (1) the forms of social interaction among the elderly at the "Gau Mabaji" Center in Romangloe Village, Bontomarannu District, Gowa Regency; (2) the forms of interaction between the elderly and caregivers/staff at the same center; and (3) the impacts of such social interactions on the elderly. This is a descriptive study using a qualitative approach. The research involved eight informants, consisting of four elderly individuals aged over 70 and four social workers. Data were collected through observation, interviews, and documentation, with data validity ensured through triangulation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing.The results of the study show that: (1) social interaction among the elderly tends to be simple and falls into two categories: associative and dissociative, influenced by similarities in age, life experiences, and emotional needs; (2) interactions between the elderly and caregivers are more complex due to differing social roles, leading to various forms of interaction ranging from cooperation to conflict, depending on emotional, professional, and interpersonal communication factors; and (3) social interactions have both positive and negative impacts on the elderly.